Femtosecond Laser Assisted Cataract Surgery in White Cataract - Jeewan Singh Titiyal; Tarun Arora (Delhi Journal of Ophthalmology)
Aim: To demonstrate application of femtosecond laser technology in patients with white cataract. Methods: Video-based description of successful management of intumescent white cataract with femtosecond laser technology. Results: We performed femtosecond laser assisted cataract surgery in multiple patients with different morphologies of white cataract. Successful completion of capsulotomy along with intraocular lens implantation in the bag was achieved in all the cases. No case had extension of capsulotomy upto the periphery. Conclusion: Femtosecond laser technology has revolutionized the management of difficult cataract case scenarios especially intumescent white cataract. Intraocular lens implantation in the bag with ideal capsular margin overlap can be achieved with ease in most cases.